2012
DOI: 10.1007/s10637-011-9772-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose-escalating study of ES-285 given as a three-hour intravenous infusion every three weeks in patients with advanced malignant solid tumors

Abstract: Dose level VIII (200 mg/m(2)) was considered the MTD, and dose level IX (160 mg/m(2)) was defined as the RD. Limited antitumor activity was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…However, in a phase I trial of doxSA conducted in patients with advanced solid tumors, doxSA showed poor antitumor activity and caused many adverse reactions, including mild-to-moderate nausea, pyrexia, injection site reactions, and vomiting (27)(28)(29). In addition, some patients developed neuropathy and liver damage (27)(28)(29). Thus, these results provide clinical evidence that, at high doses, doxSA causes tissue damage.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, in a phase I trial of doxSA conducted in patients with advanced solid tumors, doxSA showed poor antitumor activity and caused many adverse reactions, including mild-to-moderate nausea, pyrexia, injection site reactions, and vomiting (27)(28)(29). In addition, some patients developed neuropathy and liver damage (27)(28)(29). Thus, these results provide clinical evidence that, at high doses, doxSA causes tissue damage.…”
Section: Discussionmentioning
confidence: 90%
“…Purified doxSA can induce rearrangement of actin stress fibers (25) and cause apoptosis and sup- pression of cancer cell proliferation (24). However, in a phase I trial of doxSA conducted in patients with advanced solid tumors, doxSA showed poor antitumor activity and caused many adverse reactions, including mild-to-moderate nausea, pyrexia, injection site reactions, and vomiting (27)(28)(29). In addition, some patients developed neuropathy and liver damage (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, plasma DSL levels have been shown to associate also with the incidence and severity of paclitaxel-induced peripheral neuropathy in breast cancer patients (Kramer et al 2015). DSL were shown to have pronounced neurotoxic effects on neurite formation in cultured sensory neurons (Penno et al 2010) and in phase I clinical trials where deoxy-sphinga-nine was tested for its chemotherapy potential; the trials were discontinued due to patients developing severe in some cases fatal neuropathy (Baird et al 2009; Schöffski et al 2011; Massard et al 2012). Studies in an animal model of HSAN1 and in HSAN1 patients suggest that oral supplementation with L-serine reduces plasma DSL concentration (Garofalo et al 2011) and raises the prospect of a treatment option to modulate plasma DSL levels.…”
Section: Introductionmentioning
confidence: 99%
“…When produced in excess, the 1-deoxysphingolipids accumulate. The neurotoxicity of 1-deoxysphingolipids was shown in dorsal root ganglion (DRG) neurons in vitro (13) and in phase I clinical trials, where 1-deoxysphinganine (spisulosine, E-285) was tested for its anticancer potential; the clinical trials were terminated because some patients had severe, and in some cases fatal, neurotoxicity (16)(17)(18). Individuals with HSAN1 primarily experience a loss of sensation distributed in the distal parts of the upper and lower limbs (19), and most have neuropathic pain.…”
mentioning
confidence: 99%